Orofacial changes associated with the use of piercing in adolescents - Lumyla Rosalba Moll Legrá; Gustavo Moll Rodríguez; Virginia M. Cano Reyes; Yaimet Pérez Infante; Zenaida Ramón Montoya (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: Currently, there is an increase in the use of orofacial piercing in adolescents, especially attributable to the popularity of piercing by many icons of the moment.  Objective: To identify the orofacial changes associated with the use of piercing in adolescents from Tony Alomá high school.   Method:  A descriptive and cross-sectional study was carried out on 1 071 adolescents registered in this school center during  the 2020-2021 academic year. The analyzed variables were: wearer of the piercing, sex, causes that motivated the use of  piercing, harmful or toxic habits,  legal tutors' support, piercing type, localization, moment in which the orofacial changes appeared; local and functional orofacial changes.   Results: It was found that for every 100 schoolchildren, six had piercing and 76.8 % were female. Intraoral locations predominated on the tongue (50.0 %) and  labial frenums (41.7 %). Local orofacial changes were identified, such as the skin (38.3 %) and vascular (36.7 %) lesions, as well as  sialorrhea (31.7 %). The functional problems were represented by speech disorders (21.7 %).  Conclusions: The frequency of adolescents with piercing was low, although the most commonly used ones, being intraoral, caused skin and vascular lesions, sialorrhea and speech disorders.